Analisa Fundamental Makro, Fundamental Mikro Terhadap Nilai Perusahaan Dengan Struktur Modal, Kinerja Keuangan, Dan Struktur Kepemilikan Sebagai Variabel Intervening Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia - Nabilah Qurrotul `Aini; Hwihanus (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
This study aims to investigate the influence of macro fundamental variables (such as inflation, interest rates, and exchange rates), micro fundamental variables (such as DER, DPR, DR), as well as capital structure variables, financial performance, and ownership structure as intervening variables on firm value in the mining sector on the Indonesia Stock Exchange. This study uses a quantitative approach with secondary data from the financial statements of mining companies listed on the Indonesia Stock Exchange for the period 2010 to 2019. Data collection is done by random sampling of these companies, and data analysis uses the SmartPls 4 application to test the relationship between the variables studied. The results of this study are expected to provide a deeper understanding of how macroeconomic and microeconomic fundamental factors, as well as capital structure, financial performance, and ownership structure, contribute to firm value in the context of the mining sector in Indonesia. The practical implications of this study are expected to provide guidance to stakeholders, including company management, investors, regulators, and academics, in optimizing investment strategies and decision-making in this highly potential sector. This research can also make a theoretical contribution in expanding the understanding of the factors that influence firm value in the mining sector